Assessment of the service capability and readiness of Philippine hospitals to provide high-quality health care - Valerie Gilbert Ulep; Jhanna Uy; Lyle Casas; Christian Edward L. Nuevo (Philippine Institute for Development Studies (PIDS), 2021)
In the Philippines, decisionmakers mostly rely on access indicators in measuring health system performance. However, as the country embarks on path-breaking Universal Health Coverage (UHC) reforms, assessing healthcare quality is more important than ever. In this study, we examined the management practices and service capacity and readiness of hospitals, both structural measures of healthcare quality. Using a validated self-administered online questionnaire, we collected a wide range of data on hospital management and service delivery from selected public and private hospitals. Our findings reveal the longstanding challenges in hospital management and their limitations to provide even the most rudimentary components of medical care - diagnostics and drugs. Our recommendations revolve around the systematic collection of healthcare quality indicators and the use of incentives and grants to facilitate the collection, measurement, and submission of data from facilities.
Keywords: 330; Healthcare quality; service capability; universal health care; Philippines